Loss of cardiac Wnt/β-catenin signalling in desmoplakin-deficient AC8 zebrafish models is rescuable by genetic and pharmacological intervention. Issue 8 (7th March 2018) - Giuliodori, Alice; Beffagna, Giorgia; Marchetto, Giulia; Fornetto, Chiara; Vanzi, Francesco; Toppo, Stefano; Facchinello, Nicola; Santimaria, Mattia; Vettori, Andrea; Rizzo, Stefania; Della Barbera, Mila; Pilichou, Kalliopi; et al.
Abstract: Aims: Arrhythmogenic cardiomyopathy (AC) is an inherited heart disease characterized by life-threatening ventricular arrhythmias and fibro-fatty replacement of the myocardium. More than 60% of AC patients show pathogenic mutations in genes encoding for desmosomal proteins. By focusing our attention on the AC8 form, linked to the junctional protein desmoplakin (DSP), we present here a zebrafish model of DSP deficiency, exploited to identify early changes of cell signalling in the cardiac region. Methods and results: To obtain an embryonic model of Dsp deficiency, we first confirmed the orthologous correspondence of zebrafish Dsp genes ( dspa and dspb ) to the human DSP counterpart. Then, we verified their cardiac expression, at embryonic and adult stages, and subsequently we targeted them by antisense morpholino strategy, confirming specific and disruptive effects on desmosomes, like those identified in AC patients. Finally, we exploited our Dsp-deficient models for an in vivo cell signalling screen, using pathway-specific reporter transgenes. Out of nine considered, three pathways (Wnt/β-catenin, TGFβ/Smad3, and Hippo/YAP-TAZ) were significantly altered, with Wnt as the most dramatically affected. Interestingly, under persistent Dsp deficiency, Wnt signalling is rescuable both by a genetic and a pharmacological approach. Conclusion: Our data point to Wnt/β-catenin as the final common pathway underlying different desmosomal AC forms and support the zebrafish as a suitable model for detecting early signalling pathways involved in the pathogenesis of DSP-associated diseases, possibly responsive to pharmacological or genetic rescue.